2021
DOI: 10.3390/su131810051
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Manufacturing Practices, Competitive Capabilities, and Sustainable Performance: Moderating Role of Environmental Regulations

Abstract: Research highlights the increasing engagement of SMEs in adopting sustainable practices to enhance their sustainable performance. This paper extends the current literature on sustainable manufacturing practices (SMPs) and SMEs’ sustainable performance by examining the mediating effect of competitive capabilities and the moderating impact of environmental regulation. Structured questionnaires were used to collect data from 288 manufacturing SMEs in China. Research findings using structural equation modeling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 101 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…In addition, future research should focus on identifying sustainable manufacturing practices used by small and medium‐sized hospitality businesses, as well as how such practices help businesses gain competitive advantages in terms of product cost, production flexibility, product quality, and delivery. This idea is similar to Ali et al's ( 2021 ).…”
Section: Post‐covid‐19 Agenda and Call For Future Researchsupporting
confidence: 85%
“…In addition, future research should focus on identifying sustainable manufacturing practices used by small and medium‐sized hospitality businesses, as well as how such practices help businesses gain competitive advantages in terms of product cost, production flexibility, product quality, and delivery. This idea is similar to Ali et al's ( 2021 ).…”
Section: Post‐covid‐19 Agenda and Call For Future Researchsupporting
confidence: 85%
“…Agyabeng-Mensah and Tang [16], Chang [109], and Shoaib et al [110] GHC2 Employee competence concerning environmental protection in our firm is better than that of our major competitors…”
Section: Ghc1mentioning
confidence: 78%
“…The metrics were used to determine if the firms engaged in green monitoring, assessment, transportation and distribution, green storage, green packaging, etc. Five items from the research of Agyabeng-Mensah and Tang [16], Chang [109], and Shoaib et al [110] were utilized to quantify the GHC of the companies. Four items from Zeng et al [61] and Ali et al [111] were then used to evaluate the mediator SP.…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al [30] adopted AHP and TOPSIS methods to compare and analyze the drivers that promote green manufacturing implementation in small and medium-sized manufacturing enterprises in India, and concluded that green supply chain management, customers' attributes, organizational practices and adoption of new/supportive technology in the organizations are dominant parameters to ensure the successful implementation of green manufacturing practices. Ali et al [31] collected relevant data of 288 SMEs in China and applied structural equation modeling with partial least squares to analyze the obtained receipts. The results showed that sustainable manufacturing practices make SMEs more competitive.…”
Section: Drivers Of Sustainable Precision Manufacturingmentioning
confidence: 99%